Diversity of Staphylococcus pseudintermedius in carriage sites and skin lesions of dogs with superficial bacterial folliculitis: potential implications for diagnostic testing and therapy. Issue 4 (21st May 2018) - Larsen, Rikke Friis; Boysen, Lene; Jessen, Lisbeth Rem; Guardabassi, Luca; Damborg, Peter
Abstract : Background: Staphylococcus pseudintermedius is genotypically diverse within the canine population and multiple strains may colonize individual dogs at any given time. If multiple strains with distinct antimicrobial resistance profiles are present in superficial bacterial folliculitis (SBF), sampling a single skin lesion for culture and antimicrobial susceptibility testing (AST) might be inadequate to select effective therapy. Hypothesis/Objectives: To investigate S. pseudintermedius diversity in carriage sites and lesions of dogs with SBF. Animals: Fourteen dogs with SBF. Methods: Staphylococcus pseudintermedius isolates obtained from perineum, gingiva and four to six skin lesions per dog were subjected to pulsed‐field gel electrophoresis (PFGE) and AST to assess diversity between lesions. For two dogs, 14–16 isolates per lesion were included in the analysis to assess diversity within lesions. Results: Analysis of one isolate per lesion revealed one to four strains displaying unique PFGE profiles, and up to three unique antimicrobial resistance (AMR) profiles for each dog. Multiple pustules from the same dog always harboured the same strain, whereas papules, crusts and collarettes did not. Up to four strains with distinct AMR profiles were isolated from the same lesion in two dogs. In 12 dogs, at least one carriage site strain also was represented in lesions. Conclusions and clinical importance: Lesions of SBF may harbour multiple S. pseudintermedius strains with distinct antimicrobial resistance profiles. Pustules are the best target for bacterial culture. It remains unclear whether isolation of different strains from other lesion types is a consequence of contamination or co‐infection by multiple strains. Abstract : Background – Staphylococcus pseudintermedius is genotypically diverse within the canine population and multiple strains may colonize individual dogs at any given time. If multiple strains with distinct antimicrobial resistance profiles are present in superficial bacterial folliculitis (SBF), sampling a single skin lesion for culture and antimicrobial susceptibility testing might be inadequate to select effective therapy.Hypothesis/Objectives – To investigate S. pseudintermedius diversity in carriage sites and lesions of dogs with SBF.Conclusions and clinical importance – Lesions of SBF may harbour multiple S. pseudintermedius strains with distinct antimicrobial resistance profiles. Pustules are the best target for bacterial culture. It remains unclear whether isolation of different strains from other lesion types is a consequence of contamination or co‐infection by multiple strains.